Environmental characteristics and type 1 diabetes: students' perspectives on diabetes management in college - Malova, Ekaterina; Harrison, Tyler R. (Frontiers in Communication, 2023)
Introduction Type 1 diabetes is a chronic illness requiring immense lifestyle changes to reduce the chance of life-threatening complications, which can be especially challenging during the time of transition to college. This study applies a communication design perspective to explore how students with type 1 diabetes interpret their experiences in college and what meanings they attribute to those experiences. Specifically, this study sheds light on physical and social environmental components affecting students' diabetes management. Methods Study participants were recruited from the College Diabetes Network (CDN). A total of twenty students with type 1 diabetes participated in the study. A qualitative descriptive study design with an ethnographic interview approach was applied. Results Four cultural themes emerged from the analysis: (1) Food environment, (2) Structural environment, (3) Academic life, and (4) Social life. The findings illustrate how food outlets and food accessibility, safe spaces for insulin injections, comfortable living spaces, availability of health support services, and diabetes-friendly classroom regulations constitute a higher-level environmental system affecting students' wellbeing. They also highlight a complex relationship between structural barriers to diabetes management, health disclosure, and public stigma. Discussion Results from this study advance scholarship on diabetes care in the population of emerging adults by offering insights into how college students with T1D transition to college and manage type 1 diabetes. Overall, students with T1D have specific needs beyond those of the general student population. Thus, necessary modifications in the designs of existing structures should be introduced to facilitate students' assimilation into new organizational environments.